(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2022)
“Benicio Delfín Pérez” Reserve is the only protected area in the north of La Pampa province. It is a space with biodiversity, important natural and cultural values of local interest. These ambits are established by the municipality in concordance with the country’s national system of protected areas. From a University Extension Project of the UNLPam, it was proposed to create an Interactive Center to provide specific information, link society with the Reserve, and turn it, through different activities, in a place with environmental education, artistic and tourist interest, in addition to promoting the sense of belonging. Scientific, artistic and educational aspects were combined, even in the context of a pandemic. Based on this experience, we reflect about a transformative education where teaching practices and the extension project become an opportunity to generate forms of connection, accompaniment and education in the territory.